Northwestward Migration of the Northern Edge of the East Asian Summer Monsoon During the Mid‐Pliocene Warm Period: Simulations and Reconstructions. Issue 3 (8th February 2019) - Huang, Xiaofang; Jiang, Dabang; Dong, Xinxin; Yang, Shiling; Su, Baohuang; Li, Xiangyu; Tang, Zihua; Wang, Yongda
Abstract: The mid‐Pliocene ( 3.3–3.0 Ma) was the most recent warm interval during which atmospheric CO2 concentrations were similar to the present level of 400 ppmv. Therefore, it is often regarded as an analog for a near‐future climate scenario. To examine the behavior of the East Asian summer monsoon (EASM) during the mid‐Pliocene warm period, the northern edge of the EASM, a sensitive indicator of the advance and retreat of the summer monsoon rainbelt, was analyzed using the output of the Pliocene Model Intercomparison Project Phase 1. The results show a 150‐km‐northwestward migration of the northern edge of the EASM during the mid‐Pliocene compared to the preindustrial period, which is consistent with that derived from a comparison of geological records and modern observations. However, the geological records indicate a greater east‐west climatic contrast during the Pliocene than at present, which requires investigation in future modeling studies. The simulations also show a substantial increase in the large‐scale land‐sea thermal contrast between the East Asian mainland and the equatorial western Pacific during the interval of mid‐Pliocene warmth. This led to the intensification and westward extension of the western Pacific subtropical high, causing a northwestward shift of the EASM and the resulting mitigation of drought in northern China. We suggest that global warming will shift the EASM northwestward mainly via changes in the position and intensity of the western Pacific subtropical high; this requires systematic studies in the future based on meteorological observations and simulations. Key Points: Simulations show a 150‐km‐northwestward migration of the East Asian summer monsoon (EASM) during the mid‐Pliocene warm period The western Pacific subtropical high (WPSH) intensified and extended westward An enhanced east‐west climatic contrast during the mid‐Pliocene was observed in geological records compared with simulations